2022
DOI: 10.1177/15347354221130303
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Suppressed the Progression of Human Glioma Cells by Inhibiting the TGF-β1/SMAD2/3 Signaling Pathway

Abstract: Background: Previous studies have shown that berberine can inhibit glioma progression, although the underlying molecular mechanisms needed to be explored further. The aim of this study was to evaluate the suppressive effects of berberine on human glioma cells, and identify the underlying signaling pathways. Material and Methods: The cytotoxic effect of different concentrations of berberine against normal human glial cells (HEB) and 4 glioma cell lines was evaluated by the CCK-8 assay. Apoptosis was assayed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…BBR inhibited the proliferation of human glioma U-87 MG cells and induced apoptosis in the U-87 MG and LN229 cells by downregulating Bcl-2 and upregulating Bax and caspase-3. BBR exerted its effects on the proliferation, migration, invasion, and apoptosis of glioma cells by inhibiting the TGF-β1/SMAD2/3 signaling pathway [83]. Similar results have been reported in another study, showing that BBR reduce cell viability of U-87 MG cells in a concentration-and time-dependent manner, suppressed proliferation, and increased oxidative stress and early apoptosis [88].…”
Section: Effect Of Berberine On Apoptosis and Necrosis Of Transformed...supporting
confidence: 81%
See 1 more Smart Citation
“…BBR inhibited the proliferation of human glioma U-87 MG cells and induced apoptosis in the U-87 MG and LN229 cells by downregulating Bcl-2 and upregulating Bax and caspase-3. BBR exerted its effects on the proliferation, migration, invasion, and apoptosis of glioma cells by inhibiting the TGF-β1/SMAD2/3 signaling pathway [83]. Similar results have been reported in another study, showing that BBR reduce cell viability of U-87 MG cells in a concentration-and time-dependent manner, suppressed proliferation, and increased oxidative stress and early apoptosis [88].…”
Section: Effect Of Berberine On Apoptosis and Necrosis Of Transformed...supporting
confidence: 81%
“…BBR decreased ATP levels and mitochondrial membrane potential in both glioblastoma cell lines, and inhibited PI3K/Akt/mTOR pathway [82]. BBR inhibits glioma cells by inducing endoplasmic reticulum stress, disrupting mitochondrial membrane potential, downregulating ERK1/2 activity, and thus triggering apoptosis [83,84]. BBR and its derivatives are able to cross blood-brain barrier and target mitochondria as determined in a zebrafish model [85].…”
Section: Effect Of Berberine On Apoptosis and Necrosis Of Transformed...mentioning
confidence: 90%
“…Furthermore, growing evidence suggests that blocking the EMT process could be a strategic approach to halt glioblastoma's progression and dissemination. For instance, substances like curcumin, resveratrol, berberine, and sulforaphane have been shown to curtail glioblastoma cell migration and invasion by obstructing the EMT process [ [38] , [39] , [40] ]. Additionally, UA's inhibition of EMT in gastric cancer cells has been documented [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many effects of berberine pharmacology have been demonstrated to be linked to its effect on gut microbiota [ 33 ], but berberine can also affect numerous signaling pathways, including the phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt), NF-κB, the adenosine monophosphate-activated protein kinase (AMPK), the cyclic-AMP response element-binding protein (CREB), the nuclear factor erythroid 2–related factor 2 (Nrf2), and the mitogen-activated protein kinase (MAPK) pathways, thus acquiring neuroprotective effects [ 34 ]. Recently, it has been reported that berberine can inhibit the TGF-β1/SMAD2/3 signaling pathway, thus suppressing tumor progression in four human glioma cell lines [ 35 ].…”
Section: Introductionmentioning
confidence: 99%